Curriculum optimization on the basis of a multidisciplinary approach - Sergeyeva, Tetyana; Vasylieva, Kateryna; Iamnytskyi, Stanislav (ТОВ "Фінансова Рада України", 2021)
The aim of the study is to find ways of specialty curriculum optimization on the basis of a multidisciplinary approach. The state of the art is characterized by the lack of well-defined criteria for the synergistic integration of disciplines within the specialty curriculum, which necessitated the solution of the following issues: in relation to which system-forming factor to compare disciplines; how to take into account the indirect contribution of a discipline to achieving the ultimate goal of the student’s development; how to measure the efficiency/weight of the discipline in the situation of selection. To deal with these issues, the following methods were used: theoretical analysis of literature; system (quantitative and qualitative) analysis of the National Qualifications Framework, Education Standards, specialty curricula and technical discipline work programs formats and content; activity analysis of the Education Quality Guarantors, curriculum developers and lecturers of disciplines on the basis of structured questionnaires. The obtained results were compared with the efficiency of students’ training based on the correlation and factor analysis. The study allowed determining the system-forming factor in relation to which the comparison of disciplines is performed in the situation of selection; finding a way of considering the discipline direct and indirect contribution to the development of students’ strategic competences; devising a formula for measuring the discipline weight in the context of the specialty curriculum. The study revealed a direct dependence of the discipline weight on the methods of its teaching and the synergistic effect of the student development from the interaction of disciplines selected on the basis of the proposed principles. The application of the obtained results will allow optimizing specialty curricula, which will improve the quality of the education and free up time for students’ self-development. The study of the multidisciplinary approach significance has proven its inexhaustibility as a source of new scientific research.
Keywords: curriculum optimization; multidisciplinary approach; situation of selection; quality evaluation; discipline weight